The Need for Enemies : a Bestiary of Political Forms - Bailey, F. G. (Cornell University Press, 2019)
Amid the escalating hostilities of today's world, F.G. Bailey returns to the state of Orissa in the eastern India of the 1950s to consider what held a diverse collection of people together and what drove them apart. The last of Bailey's books about Orissa, The Need for Enemies, offers a ground-level view of regional politics in South Asia in the years following independence. In doing so, the book analyzes political problems that are of universal concern: incivility in public life, the inescapable dilemma of duty always in tension with interests, public consensus on what is right and good giving way to a babel of inconsistent moralities, and, not least, true believers contesting realists who see virtue in compromise. A portrait of Orissa and its leaders in 1959, the book is also a treatise on political morale. As Bailey tells the story of political and social turmoil in postcolonial India, a tale rich in ethnographic detail, he follows Orissa's politicians through a maze of inconsistencies, and makes clear the dangers that beset political cultures in a complex world of multiple competing alternatives. There is a need to simplify, Bailey suggests, and an ever present risk of making the image too simple.
Keywords: Political culture -- India -- Odisha.; Rhetoric -- Political aspects -- India -- Odisha.; Opposition (Political science); Enemies.; Political psychology.; Odisha (India) -- Politics and government.; Discours politique -- Inde -- Odisha.; Opposition (Science politique); Ennemis.; Psychologie politique.; POLITICAL SCIENCE -- History & Theory.; Enemies; Political culture; Political psychology; Politics and government; Rhetoric -- Political aspects; India -- Odisha